2010
DOI: 10.1111/j.1365-2699.2010.02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs were determined by geological processes and climate change in the Late Cenozoic

Abstract: Aim Our aims were to assess the phylogeographic patterns of genetic diversity in eastern Mediterranean water frogs and to estimate divergence times using different geological scenarios. We related divergence times to past geological events and discuss the relevance of our data for the systematics of eastern Mediterranean water frogs. Location The eastern Mediterranean region. Methods Genetic diversity and divergence were calculated using sequences of two protein-coding mitochondrial (mt) genes: ND2 (1038 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 77 publications
(106 reference statements)
1
106
1
10
Order By: Relevance
“…For instance, Ophisops elegans shows four distinct genetic lineages in Anatolia (Kyriazi et al, 2008). The Anatolian water frogs exhibit a similar pattern with various lineages having been identified (Plötner et al, 2001;Akın et al, 2010). Fritz et al (2007) revealed the existence of several mtDNA varieties of Testudo graeca in Anatolia, that were assigned to specific level, and were also confirmed in some cases by a thorough morphological approach (Türkozan et al, 2010).…”
Section: Phylogenetic Resolution Of the Anatololacerta Species Complexmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, Ophisops elegans shows four distinct genetic lineages in Anatolia (Kyriazi et al, 2008). The Anatolian water frogs exhibit a similar pattern with various lineages having been identified (Plötner et al, 2001;Akın et al, 2010). Fritz et al (2007) revealed the existence of several mtDNA varieties of Testudo graeca in Anatolia, that were assigned to specific level, and were also confirmed in some cases by a thorough morphological approach (Türkozan et al, 2010).…”
Section: Phylogenetic Resolution Of the Anatololacerta Species Complexmentioning
confidence: 91%
“…Particularly in the south, the Anatolian mountains played an important role in speciation and definition of biogeographical subregions, promoting endemisms and great intraspecific genetic diversity in this area (Çıplak, 2003, 2004 and references therein). Accordingly, several cryptic genetic lineages of amphibians and reptiles showing continuous geographic distributions in Anatolia have been revealed (Kyriazi et al, 2008;Plötner et al, 2001;Akın et al, 2010;Fritz et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…This resulted in a high genetic heterogeneity of the introduced frogs because substantial differences exist among taxa within the ''P. ridibundus'' group (Holsbeek et al 2008;Plénet et al 2009;Akin et al 2010;Plötner et al 2010). Especially in France, the expansion range has increased since the middle of the twentieth century because of repeated introductions of live water frogs (Pagano et al 2001;Schmeller et al 2005; but also see Plötner 2005).…”
Section: Introductionmentioning
confidence: 96%
“…They stated that the Anatolian peninsula is a predominantly mountainous area whose diverse geomorphology produces many different climatic regions and vegetation types. In addition, Akın et al (2010) indicated that 2 clades of water frogs may have split from the uplift of the Taurus Mountains, and they also showed phylogeographic patterns of genetic diversity for water frogs as determined by geological processes and climate in Anatolia. During the Tertiary and Quaternary, Anatolia acted either as a bridge or as a barrier for species dispersal between Asia and Europe, providing a natural pathway or acting as a vicariant agent (Tchernov, 1992).…”
Section: Discussionmentioning
confidence: 98%